2016
DOI: 10.1097/mpa.0000000000000459
|View full text |Cite
|
Sign up to set email alerts
|

Differential Protein Expression in Small Intestinal Neuroendocrine Tumors and Liver Metastases

Abstract: Objectives Small intestinal neuroendocrine tumors (SI-NETs) are often detected after they have become metastatic. Using a novel protein array, we identified pathways important in SI-NET metastasis development in surgically resected patients. Methods Paired primary tumors and liver metastases from 25 patients undergoing surgical resection for metastatic SI-NETs were harvested. Extracted proteins were separated by SDS gel, and multiplex immunoblots were performed with 136 antibodies. Significant Analysis of Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…In-silico pathway analysis revelead that cell cycle pathways were found to be significantly mutated in the primary lesion, whereas genes regulating adherence junction stability and disassembly were identified in the metastases group. This correlates to protein expression data of a study of Kim et al, where proteins involved in cell cycle and proliferation were found to be differentially expressed in primary lesions and metastasis 21 . However, functional data of metastasis development of SI-NET are still due and further studies are warranted.…”
Section: Discussionsupporting
confidence: 89%
“…In-silico pathway analysis revelead that cell cycle pathways were found to be significantly mutated in the primary lesion, whereas genes regulating adherence junction stability and disassembly were identified in the metastases group. This correlates to protein expression data of a study of Kim et al, where proteins involved in cell cycle and proliferation were found to be differentially expressed in primary lesions and metastasis 21 . However, functional data of metastasis development of SI-NET are still due and further studies are warranted.…”
Section: Discussionsupporting
confidence: 89%
“…It remains a time-consuming and subjective process and produces a qualitative or semiquantitative assessment of protein expression because of the nonspecific stain or background noise. As technology advanced and high-throughput demand increased over the last decade, the TMA gradually began to be widely used in both research and clinical fields 36 , 37 . TMA contains many small representative tissue cores of formalin-fixed paraffin-embedded (FFPE) or frozen blocks from hundreds of different cases assembled in an array fashion on a single histologic slide, and therefore allows a large-scale antibody-based molecular analysis of multiple samples at the same time 37 .…”
Section: High-throughput Proteomic Techniquesmentioning
confidence: 99%